Prevalence of Helminthic Infection in Capra hircus L. from Ahmednagar District (M.S.) - Dhole J. S., D.S Tambe, H.J. Wankhede and (Recent Research in Science and Technology, 2011)
The present study deals with the prevalence of helminthic infection in Capra hircus during period of July 2008 to June 2009 from Ahmednager district (M.S.). Out of 300 samples examined 255 (85%) found to be infected with the helminth parasites. The seasonal variation of gastro-intestinal helminthic infection shows the higher prevalence occurs in monsoon (95%) followed by winter (87%) and summer (73%) because of easy dispersal of larvae in pasture resulting is increased in contact with the host and the parasites. Among the helminth parasites found the maximum incidence occurs is of cestode parasites in all seasons (48.33%) followed by nematodes (26.66%) and trematode (10%) respectively.